2022
DOI: 10.1161/circulationaha.122.059713
|View full text |Cite
|
Sign up to set email alerts
|

TBX20 Improves Contractility and Mitochondrial Function During Direct Human Cardiac Reprogramming

Abstract: Background: Direct cardiac reprogramming of fibroblasts into cardiomyocytes has emerged as a promising strategy to remuscularize injured myocardium. However, it is insufficient to generate functional induced cardiomyocytes from human fibroblasts using conventional reprogramming cocktails, and the underlying molecular mechanisms are not well studied. Methods: To discover potential missing factors for human direct reprogramming, we performed transcriptomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…While this manuscript was under review, Tang et. al independently identified TBX20 as a cardiac reprogramming factor 45 . In their study, addition of TBX20 to GMT + miR133 resulted in cells with more fully activated cardiac conduction systems.…”
Section: Discussionmentioning
confidence: 99%
“…While this manuscript was under review, Tang et. al independently identified TBX20 as a cardiac reprogramming factor 45 . In their study, addition of TBX20 to GMT + miR133 resulted in cells with more fully activated cardiac conduction systems.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Lalit et al [ 161 ] showed that mesoderm posterior bHLH transcription factor 1 (MESP1), GATA4, TBX5, NK2 homeobox 5 (NKX2-5), and BAF60C (SMARCD3, SWI/SNF related, matrix associated, actin dependent regulator of chromatin, subfamily D, member 3) expressed in fibroblasts produce a progenitor population that gives rise to cardiomyocytes, endothelial cells, and mural cells in myocardial infarction mice models. Recent study also suggests that the cardiac gene TBX20 (T-box transcription factor 20) enhances myocardial reprogramming induced by the MGT133 reprogramming cocktail (MEF2C, GATA4, TBX5, and miR-133) [ 162 ]. In summary, transcription factor combinations play an important role in transforming fibroblasts into cardiomyocytes in mice.…”
Section: Approaches and Challenges For Heart Regenerationmentioning
confidence: 99%
“…Since the development of GMT-derived iCMs, many have tried to further optimize the transdifferentiation protocol and conditions. The addition of other transcription factors associated with cardiomyocyte function and maturation has been a common approach to further optimize the transdifferentiation process (Addis et al, 2013;Singh et al, 2021;Song et al, 2012;Y. Tang et al, 2022).…”
Section: Heterocellular Reprogrammingmentioning
confidence: 99%